Feminist Studies: A Guide to Intersectional Theory, Methodology and Writing - Lykke, Nina (Routledge Advances in Feminist Studies and Intersectionality, 2010)
In this book, feminist scholar Nina Lykke highlights current issues in feminist theory, epistemology and methodology. Combining introductory overviews with cutting-edge reflections, Lykke focuses on analytical approaches to gendered power differentials intersecting with other processes of social in/exclusion based on race, class, and sexuality. Lykke confronts and contrasts classical stances in feminist epistemology with poststructuralist and postconstructionist feminisms, and also brings bodily materiality into dialogue with theories of the performativity of gender and sex. This thorough and needed analysis of the state of Feminist Studies will be a welcome addition to scholars and students in Gender and Women’s Studies and Sociology. Part I: What is Feminist Studies? 1. A Guide’s Introduction 2. A Postdisciplinary Discipline 3. Undoing Proper Research Objects Part II: To Theorize Intersectional Gender/Sex 4. Intersectional Gender/Sex: A Conflictual and Power-Laden Issue 5. Theorizing Intersectionalities: Genealogies and Blind Spots 6. Genealogies of Doing 7. Making Corporealities Matter: Intersections of Gender and Sex Revisited Part III: To Re-tool the Thinking Technologies 8. Rethinking Epistemologies 9. Methodologies, Methods and Ethics 10. Shifting Boundaries between Academic and Creative Writing Practices Part IV: To Use a Feminist Hermeneutics 11. Doing and Undoing the God-Trick: Analytical Examples Nina Lykke is professor of Gender Studies at Linköping University, Sweden. She is also the author of Between Monsters, Goddesses and Cyborgs: Feminist Confrontations with Science, Medicine and Cyberspace (with Rosi Braidotti) (ZED, London 1996), Cosmodolphins. Feminist Cultural Studies of Technology, Animals and the Sacred (with Mette Bryld) (ZED, London 2000) and Bits of Life. Feminism at the Intersections of Media, Bioscience, and Technology (with Anneke Smelik) (Washington University Press, 2008).